Tensile Strength Behavior Of Concrete Containing Seawater, Sea Sand Together With Steel Fibers - Adnan, Adnan; Tandon, Meredith; Xavier, Murphy (Journal of Moeslim Research Technik, 2024)
The characteristics of concrete are that it has high compressive strength and low tensile strength. To increase the tensile strength of concrete, it is necessary to use fiber as a constituent material for concrete. This study aims to evaluate and compare the tensile strength value of concrete containing sea sand and seawater with or without steel fiber reinforcement stolen by seawater for 28 days, as well as analyze the homogeneity of the concrete mixture. The materials used are composite portland cement, gravel, sea sand and seawater and 3D 80/60 BG dramix. Determination of the volume fraction of steel fibers is 0% - 2.5% to the weight of cement. Testing the tensile strength of concrete using the split tensile strength method. The results tensile strength showed that the value of seawater concrete increased due to the reinforcement of steel fiber, with the addition of 2.5% steel fiber, which was 17.8%. The tensile strength value of seawater concrete increased due to the reinforcement of steel fiber, with the addition of 2.5% steel fiber, which is 24.2%. Overall, all test specimens showed uniformity or homogeneous amounts of gravel and steel fibers in all four cross-sectional areas.